2014
DOI: 10.3390/rs6032296
|View full text |Cite
|
Sign up to set email alerts
|

Pan-Arctic Climate and Land Cover Trends Derived from Multi-Variate and Multi-Scale Analyses (1981–2012)

Abstract: Arctic ecosystems have been afflicted by vast changes in recent decades. Changes in temperature, as well as precipitation, are having an impact on snow cover, vegetation productivity and coverage, vegetation seasonality, surface albedo, and permafrost dynamics. The coupled climate-vegetation change in the arctic is thought to be a positive feedback in the Earth system, which can potentially further accelerate global warming. This study focuses on the co-occurrence of temperature, precipitation, snow cover, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 84 publications
2
24
0
Order By: Relevance
“…Local permafrost degradation resulting in thaw pond development and drowning of shrubs could have prevented net shrub expansion (Nauta et al 2015). The negative precipitation trend is not unique to the study area, but also occurred in some other locations, particularly in the High Arctic (Urban et al 2014). We used the KNMI Climate Change Atlas tool (http://climexp.knmi.nl/atlas) to generate a map of summer (JJA) precipitation trends over the years 1991-2015 for the Arctic land based on observations (CRU TS 3.22 dataset).…”
Section: Discussion Climatic Change and Ramet Establishmentmentioning
confidence: 99%
“…Local permafrost degradation resulting in thaw pond development and drowning of shrubs could have prevented net shrub expansion (Nauta et al 2015). The negative precipitation trend is not unique to the study area, but also occurred in some other locations, particularly in the High Arctic (Urban et al 2014). We used the KNMI Climate Change Atlas tool (http://climexp.knmi.nl/atlas) to generate a map of summer (JJA) precipitation trends over the years 1991-2015 for the Arctic land based on observations (CRU TS 3.22 dataset).…”
Section: Discussion Climatic Change and Ramet Establishmentmentioning
confidence: 99%
“…Precipitation increases have also been observed over both North America and Eurasia over the past century (Nicholls et al, 1996;Groisman et al, 1991). Urban et al (2014) describe the co-occurrence of these climatic and ecosystem changes. Here we investigate increasing GPP of terrestrial ecosystems of northern Eurasia and determine the relative attribution arising through changes in several geophysical quantities, hereinafter referred to as "environmental variables", as they potentially drive observed temporal changes in vegetation productivity.…”
Section: Introductionmentioning
confidence: 90%
“…We consequently do not analyse the influence of CO 2 concentration. While some studies have focused on terrestrial ecosystems of the pan-Arctic (Urban et al, 2014;Myneni et al, 1997;Guay et al, 2014;Kim et al, 2014) or the high latitudes of North America (Goetz et al, 2005;Buermann et al, 2013;Thompson et al, 2006), few studies have investigated the relative role of different environmental variables on increasing GPP of northern Eurasia. Therefore, we assess in this study how vegetation productivity trends in northern Eurasia are influenced by the environmental variables air temperature, precipitation, cloudiness, and forest fire.…”
Section: Introductionmentioning
confidence: 99%
“…Although the patterns are geographically fragmented (Elsakov and Teljatnikov, 2013;Barichivich et al, 2014;Guay et al, 2014), the northern biomes (tundra and foresttundra) demonstrate widespread increase of the vegetation productivity ("greening"). Its attribution to tall shrub and graminoids in tundra ecosystems (Frost and Epstein, 2014) and enhanced tree growth in forest-tundra ecosystems (Urban et al, 2014) suggested that we observe transitions to alternative, potentially more productive ecosystems rather than anomalously enhanced biological productivity in response to global warming Macias-Fauria et al, 2012). These environmental shifts have been unfolding for at least the last 3 decades (Keeling et al, 1996;Myneni et al, 1997) albeit at a slower pace since 2003 (Bhatt et al, 2013).…”
Section: Introductionmentioning
confidence: 99%